Autoimmune Encephalitis. An Analysis of Three Cases - G. R. Ramazanov; E. V. Shevchenko; E. M. Bardina; Kh. V. Korigova; E. A. Kovaleva; L. Kh.-B. Akhmatkhanova; I. S. Aliev; M. V Sinkin (Неотложная медицинская помощь)
The diagnosis of diseases from the group of autoimmune encephalitis (AE) requires a detailed analysis of clinical data and correlation of results from a wide range of laboratory and instrumental research methods. This article presents three clinical cases of patients with AE. In one patient, AE was associated with a malignant neoplasm, in the second one – with the novel coronavirus infection, and in the third patient, no comorbid pathology was detected. The specific type of encephalitis was determined for each of the three patients. The diagnosis of “autoimmune limbic encephalitis” was established in two patients based on visualization of changes in the medial temporal structures in the magnetic resonance imaging of the brain, detection of pathological bioelectrical activity in the temporal lobe cortex in electroencephalography, and pleocytosis in cerebrospinal fluid. The diagnosis of “anti-NMDA receptor encephalitis” was made based on the detection of specific antibodies to the subunit of the corresponding receptor. Neurological deficit regression was observed in two patients after the application of combined immune therapy methods and in one patient without the use of immune therapy.